Sinkronisasi Sebagai Upaya Penyesuaian Kurikulum Sesuai Kebutuhan Dunia Industri Pada Smk Nu01 Kendal - Dwi Astarani Aslindar; Shofiatul Mila; Rizki Ridhasyah (Unika Santu Paulus Ruteng, 2023)
A huge number of vocational graduates who are jobless should be a matter to concern. One of the causes of this condition is the incompatibility of graduates with the needs of the world of work. This problem is one of the impacts of the lack of suitability of the curriculum used in vocational schools. Therefore, as one of the vocational schools, SMK NU 01 Kendal needs to synchronize the curriculum in an effort to solve such existing problem. Curriculum synchronization is carried out through collaboration with the world of industry and universities in the form of community service activity. Thus, the the curriculum suitability in producing graduates according to the needs of the business world/industry world is achieved.